2021
DOI: 10.1101/2021.08.03.454996
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A pathogenic DYT-THAP1 dystonia mutation causes hypomyelination and loss of YY1 binding

Abstract: Dystonia is a disabling disease that manifests as prolonged involuntary twisting movements. DYT-THAP1 is an inherited form of isolated dystonia caused by mutations in THAP1 encoding the transcription factor THAP1. The phe81leu (F81L) missense mutation is representative of a category of poorly understood mutations that do not occur on residues critical for DNA binding. Here, we demonstrate that the F81L mutation (THAP1F81L) impairs THAP1 transcriptional activity and disrupts CNS myelination. Strikingly, THAP1F8… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…A network model of dystonia proposes that dysfunction occurs along the pathways connecting different brain regions, including the cortex, thalamus, basal ganglia, and cerebellum [52]. In dystonia, there is a disruption in the communication and coordination between these brain areas, resulting in abnormal motor output.…”
Section: Lack Of Connection Between Different Biological Levels Of An...mentioning
confidence: 99%
“…A network model of dystonia proposes that dysfunction occurs along the pathways connecting different brain regions, including the cortex, thalamus, basal ganglia, and cerebellum [52]. In dystonia, there is a disruption in the communication and coordination between these brain areas, resulting in abnormal motor output.…”
Section: Lack Of Connection Between Different Biological Levels Of An...mentioning
confidence: 99%
“…Similarly, YY1 is crucial for peripheral myelination as mutants with conditional ablation of Yy1 in Schwann cell lineage result in severe hypomyelination (He et al, 2010). The latest report has demonstrated that the phe81leu (F81L) missense mutation in thanatos‐associated protein domain‐containing apoptosis‐associated protein 1 ( Thap1 ) gene causes a significantly reduced DNA binding of YY1 and leads to the disruption of CNS myelination (Yellajoshyula et al, 2021). Moreover, de novo YY1 ‐truncating variant has also been described as a cause of severe childhood‐onset generalized dystonia disability (Zorzi et al, 2021).…”
Section: Yy1 In Nervous System Developmentmentioning
confidence: 99%
“…Consequently, mutation in Thap1 ( Thap 1 F81L ) causes a significantly reduced DNA binding of YY1 and leads to the disruption of CNS myelination. Although Thap1 F81L normally binds DNA, it is unable to efficiently organize an active YY1‐containing co‐activator complex (Yellajoshyula et al, 2021). It is also worth adding that transcriptome analysis showed that YY1 was the most up‐regulated transcription factor in the manifesting group when compared to non‐manifesting THAP1 mutation carriers or controls (Baumann et al, 2021).…”
Section: Dystoniamentioning
confidence: 99%